UPAYA PENGELOLAAN MINIM SAMPAH RUMAH TANGGA: Management Effort for Minimum Household Waste - Sukadaryati Sukadaryati; Sarah Andini (Jurnal Silva Tropika, 2021)
The amount of solid waste generation in Indonesia is projected to increase along with the increase in population. The government has been developing various efforts to reduce and handle solid waste, including household waste and the like, through regulations and policies. This paper provides an overview of solid waste management on the household scale to support the reduction of waste generation. A literature review was carried out on data and information collection that regarding solid waste management. Undang-Undang Republik Indonesia Nomor 18 Tahun 2008 regulates the urgency and mechanism of solid waste management to improve public health and environmental quality and make waste become a resource. Public awareness and paradigm shift in waste management are essential to make it realize. The application of a zero-waste lifestyle with the concept of reduce, reuse, and recycle (3R) is a kind of community involvement. The emergence of the waste bank (bank sampah) also becomes community-based waste management activity as well as a facility of education and behavior shift in waste management. The waste bank was able to contribute to the national waste reduction and contribute to improving the community's economy. The lifestyles have changed, all levels of society get used to living a zero-waste. All of those are to get clean Indonesia by 2025.